Physical education students’ reflections about the learning outcomes of different teaching methods: a mixed methods study - Sørensen, Arne; Lagestad, Pål (Frontiers in Education, 2024)
Teaching in higher education is still mainly executed as lectures, even though research about student-active instruction methods points to more motivated students, higher enjoyment, and more optimal learning outcomes. The purpose of this study was to obtain better insight into how physical education (PE) students assessed their learning outcomes in relation to the use of different pedagogical approaches. A master's course in PE was planned and implemented using the following eight different learning approaches: lectures; practical exercises about themes in lectures; discussions during lectures; discussions outside of lectures; planning and exercises for peer students; individual work preparing to write an academic text; individual work writing the academic text; and reading for an exam. The study constituted a mixed methods study, which used quantitative data from students' evaluation of eight different learning approaches on a Likert-type scale, and in-depth qualitative data from follow-up interviews with some of the same students, with the aim of explaining the main findings.Quantitative data about the students' reflections on the learning outcomes of the different learning approaches were collected among 59 different students at three different times (2021, 2022, and 2023), after finishing a course in the fifth semester in a master's program in PE.The findings showed that the students reported achieving the highest learning outcomes from practical exercises and attaining the lowest learning outcomes from lectures. In depth interviews among seven randomly selected students were also used to obtain reflections from the students about the different learning approaches. Quantitative analyses again revealed that practical exercises produced the highest learning outcomes, while lectures resulted in the lowest learning outcomes. Qualitative analyses of the in-depth interviews indicated that practical activities enabled students to relate theory to practice, make them active, and are associated with future work, while the quality of lectures depended on characteristics of the teacher and were often experienced as long and unstimulating. According to the results, we recommend that student teachers in higher education acquire the ability to plan and execute practical lessons in relation to themes focused upon in lectures and involve students more in discussions during lectures.